2005
DOI: 10.1111/j.1532-7795.2005.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adolescents' Filial Self‐Efficacy on Quality of Family Functioning and Satisfaction

Abstract: In this prospective study, we tested a structural model in which adolescents' perceived self-efficacy to manage parental relationships affected their satisfaction with family life both directly, and indirectly, through its impact on family practices. Findings based on 380 Italian adolescents showed that perceived filial self-efficacy was linked directly and indirectly to satisfaction with family life, and that these relations held both concurrently and longitudinally. In particular, the greater adolescents per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 104 publications
(91 reference statements)
8
74
0
1
Order By: Relevance
“…In particular, increasing the agentic role that adolescents and young adults play in their relationships with their parents, such as being able to talk with their parents in tense situations, regulate and manage their own negative emotional reactions, could be a vehicle to ameliorate the quality of parent (mother)-youth interactions constructively (Caprara et al, 2005).…”
Section: Conclusion Limitations and Future Directionsmentioning
confidence: 99%
“…In particular, increasing the agentic role that adolescents and young adults play in their relationships with their parents, such as being able to talk with their parents in tense situations, regulate and manage their own negative emotional reactions, could be a vehicle to ameliorate the quality of parent (mother)-youth interactions constructively (Caprara et al, 2005).…”
Section: Conclusion Limitations and Future Directionsmentioning
confidence: 99%
“…Following Caprara et al (2005), Confirmatory Factor Analyses (CFA) were computed to differentiate the constructs of self-efficacy and perceived competence (for measuring levels of skills). Table I presents the results of the CFA tested between selfefficacy and perceived competence.…”
Section: Preliminary Analysesmentioning
confidence: 99%
“…Earlier research has shown that excessive gamblers often are introduced to gambling when they are underage (Productivity Commission Report 1999;Wynne et al 1996), thus the competitive gamblers in the youth sample show a penchant for and a predisposition to excessive gambling. The foundation for prospective excessive gambling is augmented by an early introduction to gambling, in connection with the social and cultural milieu (Bourdieu 1986a(Bourdieu , 1993 and the social cognitive environment, where young people act as both producers and products of social systems (Caprara et al 2005;Derevensky and Gupta 2001;Wynne et al 1996).…”
Section: Gambling Inclination and Students' Approach To Gamblingmentioning
confidence: 99%
“…Geographical remoteness and a requirement for cooperation will not overcome anti-social behaviour and social exclusion tendencies, but rather exacerbate it as the rural setting restricts privacy and diversity (Portes 1998;Dempsey 1990). In rural as well as in urban areas, community residents need to partake in local social activities to feel respected, valued and acknowledged (Caprara et al 2005;White and Wyn 2004: 11-14;Arthurson and Jacobs 2003). Children and young people are the most powerless and for young people this means that restrictions and opportunities are different from those of adults.…”
Section: Introductionmentioning
confidence: 99%